Analisis Pengaruh Suhu Ekstrusi dan Merek Produk terhadap Kualitas Biji Plastik Daur Ulang Limbah Botol Plastik Polyethylene Terephtalate (PET) - Sukmawati; Theresia E.P.S. Rahayu; Oto Prasadi (P3M Politeknik Negeri Cilacap, 2026)
Recycling plastic waste, especially Polyethylene Terephtalate (PET), into plastic pellets has great potential for producing environmentally friendly products. This study aims to recycle plastic waste from used mineral water bottles into plastic pellets using the pelletizing method, or the process of molding a material into pellets, with the independent variables being the brand of PET plastic bottle waste and temperature, and to determine their effect on the quality of the recycled plastic pellets produced. The quality parameters tested included moisture content, bulk density, total heavy metals Pb, PVC contamination, other contaminants, tensile strength, shape, color, and toxicity (LC50). The results showed that all parameters met the SNI 8424:2017 quality standards and had a fairly uniform color in the V120 variable, while in V135, only PVC contamination did not meet the standards, but for both variations, the shape was not uniform. The 72-hour LC50 test on all variations with a concentration of 6.5 kg/m3 showed low toxicity as it resulted in zero fish mortality.